Pengaruh E-Learning Terhadap Motivasi Belajar PAI di SMKN 1 Koto Baru, Dharmasraya - Wati, Nola Nurahma; Aprison, Wedra (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Students who experience repetitive conventional learning get disinterested and start doing things outside of the learning process. The utilization of e-learning is one of the things that might motivate pupils to study. Determining the degree of the "impact of e-learning on students' learning motivation in PAI at SMK Negeri 1 Koto Baru" is the aim of this research. 73 pupils were chosen from a total sample of 278 students in this quantitative study that used a correlational strategy. Random sampling served as the sample technique. Questionnaires were used to gather data, and hypothesis testing was carried out. With a correlation value of 0.670, it is possible to establish that e-learning has an impact on students' desire to study. This number suggests a strong correlation. The findings indicate that rtable (0.235) is less than rcount (0.670). Thus, e-learning has an impact on PAI learning motivation at SMK Negeri 1 Koto Baru, as shown by the rejection of Ho and acceptance of Ha.